Anabolic steroid consumption among gym-goers in Amman: knowledge, attitudes, and behaviors - AlKasasbeh, Walaa; Shlool, Hatem; Alnaimat, Sajeda (Frontiers in Sports and Active Living, 2024)
Gym members are particularly susceptible to using Anabolic-androgenic steroids (AAS) to enhance their physical training and performance. Research conducted worldwide indicates a significant incidence of AAS use among athletes and gym members, many of whom use AAS that are neither proven safe nor legal. This study aims to identify the prevalence of AAS use among gym attendees in Amman, Jordan, and to understand the associated knowledge, attitudes, and behaviors. The research involved 399 participants from 35 randomly selected gyms in the metropolitan area. Participants were selected using a cluster sampling technique to ensure a diverse and representative sample. A self-administered questionnaire was used for data collection.The results revealed significant associations between AAS use, knowledge, attitudes, behavioral factors, and demographics, including gender, age, exercise frequency, reasons for exercise, and total exercise duration. The study employed statistical methods to analyze the data and examine relationships between different variables. Chi-square tests were used to assess the statistical relationships between AAS use and categorical variables. Logistic regression was employed to identify predictors of AAS use. The findings underscore the necessity for targeted interventions to address misconceptions and encourage safer practices, contributing to the overall health and well-being of gym-goers in Amman. The study provides valuable insights for shaping strategies, policy adjustments, and educational initiatives aimed at curbing AAS misuse and fostering a healthier gym culture in the region.